Creating memes, Sweding movies, and other digital performances : adaptation online - Gratch, Lyndsay Michalik (Studies in new media., 2017)
"This book shows how traditional notions of the processes and products of creative adaptation are evolving online. It provides a vocabulary to analyze, discuss, and theorize about the implications of online forms of adaptation and highlights the potential and possible ethical quandaries of adaptation online"--